Workplace bullying and interpersonal conflicts: the moderation effect of supervisor’s power - Arenas, A. (2015)
Workplace bullying is considered the final stage of a prolonged conflict where there is a power imbalance between the affected parties and where emotional and relational problems exist. Thus, this study aims to explore the role of perceptions of supervisor’s power bases on the relationship of conflict and bullying at work. A cross-sectional survey study was conducted (N = 211). Results support a moderated-mediation model in which relationship conflict mediates the association between task conflict and workplace bullying, suggesting a conflict escalation process in bullying situations. In addition, establishing personal power bases seems to reduce the intensity of the link between task conflict and relationship conflict and, in turn, workplace bullying, whereas establishing positional power bases was not related to this association. Practical implications for bullying prevention are discussed.